Spin experiments with a biased ball. (19th August 2019) - Cross, Rod
Abstract: Experimental and theoretical results are presented concerning spin and precession of a biased ball. The ball was biased by attaching a small ball to the top surface of a larger ball, and the balls were spun about a vertical axis. The small ball remained near the top of the large ball for up to about 60 s before falling slowly to a point below the equator of the large ball. The long-term stability of this arrangement appears to contradict previous observations with hurricane balls (two balls of equal mass joined together) that show that one ball cannot rise more than about twenty degrees above the equator of the other ball. The stability arises from the fact that the balls precessed about a vertical axis close to but not coincident with the centre of mass. Results are also presented for cases where (a) the small ball was observed to rise above the equator of the large ball, starting from a point below the equator and (b) the balls rolled about a horizontal axis while precessing about a remote vertical axis.